Exploring the Use of Skin Staples for Bowel Anastomosis: A Scoping Review - Saburi Oyewale; Olayinka Adewumi; Azeezat Ariwoola (Iranian Journal of Colorectal Research)
Background: Intestinal staplers have revolutionized gastrointestinal surgery by facilitating faster bowel anastomoses, achieving outcomes comparable to hand-sewn techniques. However, their high cost restricts routine use in resource-limited settings, leading to increased interest in using skin staples for bowel anastomoses. Therefore, we aim to evaluate the use of skin staples for this purpose. Methods: We conducted a systematic search of databases using the search terms “skin staples” and “bowel anastomoses.” Studies that focused on the use of skin staples for bowel anastomoses were included, while abstracts, animal studies, and conference papers were excluded. The risk of bias was assessed with the ROBINS-I tool. Results: Two non-randomized studies involving 115 patients met the inclusion criteria. The majority of cases involved small bowel-to-small bowel anastomoses (74.8%), with cancer being the primary indication (80%). Postoperative complications included two cases of pelvic collections and one case of intestinal obstruction, all of which were managed non-operatively. No anastomotic leaks were reported. The risk of bias was moderate due to unclear patient selection processes. Conclusion: While the use of skin staples for bowel anastomoses appears to be safe, with no reported anastomotic leaks and minimal complications in the included studies, it is important to note the small sample sizes of these studies. This highlights the need for further multicenter randomized controlled trials to validate these findings and compare outcomes with conventional staplers and hand-sewn methods. The potential of skin staples as a viable alternative in resource-limited settings is promising; however, further research is necessary to confirm this.